2021
DOI: 10.29140/jaltcall.v17n1.304
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing augmented reality to enhance the vocabulary of young EFL learners

Abstract: This study seeks to contribute to the small, but growing area of research regarding technology potential in the field of vocabulary research. The study aims to determine the usefulness of augmented reality (AR) technology in EFL vocabulary learning. An experiment was conducted to examine young learners’ motivation and vocabulary retention. The current study employed two instruments: a pre-post-delayed test and an interview. The participants (=73) were primary school sixth-graders (11–12 years old) and were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
2
18
1
Order By: Relevance
“…On the other hand, the above result is contradictory to results reported by a few previous studies in different contexts (Alemi et al, 2021;Binhomran & Altalhab, 2021;Maftoon et al, 2021;Nakata, 2008). These studies reported no statistically significant differences in the vocabulary posttests between the experimental groups that learned vocabulary through technological tools and the control groups that learnt vocabulary through traditional approaches.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…On the other hand, the above result is contradictory to results reported by a few previous studies in different contexts (Alemi et al, 2021;Binhomran & Altalhab, 2021;Maftoon et al, 2021;Nakata, 2008). These studies reported no statistically significant differences in the vocabulary posttests between the experimental groups that learned vocabulary through technological tools and the control groups that learnt vocabulary through traditional approaches.…”
Section: Discussioncontrasting
confidence: 77%
“…The above result was also supported by other studies on the use of Augmented Reality (AR) technology, which is a form of virtual reality where learners learn new vocabulary through audio and visual media, including its audio pronunciation and pictures and video materials that explain the meaning and use of new vocabulary. For instance, Binhomran and Altalhab (2021) them, despite the different mean scores of both CALL-supported and traditional approach-supported groups of learners in vocabulary performance, these differences were not statistically significant. The researchers attributed this result to several probable factors affecting learners' retention of vocabulary, their lack of technical knowledge, distraction, and chaos resulting from CALL-supported vocabulary learning.…”
Section: The Effect Of Computer-assisted Vocabulary Learning On Learn...mentioning
confidence: 84%
See 3 more Smart Citations